2016
DOI: 10.1186/s13068-016-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the two-step treatment with ionic liquids and alkali for enhancing enzymatic hydrolysis of Eucalyptus: chemical and anatomical changes

Abstract: BackgroundThe biomass recalcitrance resulting from its chemical compositions and physical structures impedes the conversion of biomass into fermentable sugars. Pretreatment is a necessary procedure to increase the cellulase accessibility for bioconversion of lignocelluloses into bioethanol. Alternatively, ionic liquids, a series of promising solvents, provide unique opportunities for pretreating a wide range of lignocellulosic materials. In this study, a two-step treatment including ionic liquids pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 63 publications
(68 reference statements)
4
30
0
Order By: Relevance
“…The same effect could be observed in case of IL and IL+NaOH pretreated CS as compared to the untreated CS spectra. The another lignin aromatic skeletal vibrational peak at 1505 cm IL+NaOH pretreated CS and SB substrates possibly indicating the removal of amorphous cellulose [6]. The peak at 1373 cm −1 corresponding to C-H deformation in cellulose and hemicelluloses showed slight decrease in intensities in case of IL+NaOH pretreated SB compared to the increase in SB-Na whereas in case of CS, no prominent change was observed at the same frequency [32].…”
Section: Ftir Spectra Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…The same effect could be observed in case of IL and IL+NaOH pretreated CS as compared to the untreated CS spectra. The another lignin aromatic skeletal vibrational peak at 1505 cm IL+NaOH pretreated CS and SB substrates possibly indicating the removal of amorphous cellulose [6]. The peak at 1373 cm −1 corresponding to C-H deformation in cellulose and hemicelluloses showed slight decrease in intensities in case of IL+NaOH pretreated SB compared to the increase in SB-Na whereas in case of CS, no prominent change was observed at the same frequency [32].…”
Section: Ftir Spectra Analysismentioning
confidence: 80%
“…Similarly, Li et al [6] showed the decreased roughness of Eucalyptus cell wall after [Bmim][OAc] pretreatment. The re-location of lignin in case of [Emim][OAc]+Na pretreated CS could also be co-related with the increased enzymatic saccharification as shown in Figure 4(a).…”
Section: Afm Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A promising replacement for citrate buffer could be a sodium acetate buffer, which is also used during enzymatic hydrolysis of lignocellulose biomass [18,19]. This buffer contains acetate, which was shown in our previous study to greatly improve microalgae growth [13], and therefore can constitute an additional carbon source for microalgae cultivated on lignocellulosic hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alkaline pretreatment, instead of diluted acid pretreatment, was applied before enzymatic hydrolysis. Alkaline pretreatment with the use of NaOH was reported as an effective method to remove hemicellulose and Klason lignin from birch [17], cedar [18] and eucalyptus [18,19] wood, resulting in the increase in cellulose exposure and improvement of cellulose conversion to glucose during enzymatic hydrolysis [18,19]. Temperature of pretreatment and NaOH concentration are crucial parameters determining removal rate of hemicellulose and lignin from wood, and subsequent cellulose hydrolysis.…”
Section: Pretreatment and Enzymatic Hydrolysis Of Woodmentioning
confidence: 99%